GENERA-Z TANGGUH; GEN-Z OF PRIMAGANDA JOMBANG HIGH SCHOOL EMPOWERMENT TOWARDS HANDLING OF COVID-19 IN THE SCHOOL WITH PREVENTIVE AND 4T (TRACING, TEXTING, TESTING, TREATMENT) EFFORT - Akhiyan Hadi Susanto; Rahma Micho Widyanto; Shila Wisnasari; Nurona Azizah; Rustiana Tasya Ariningpraja (Caring : Jurnal Pengabdian Masyarakat, 2022)
The government has started to require limited face-to-face learning starting in July 2021. Until now, cases of Covid-19 transmission are still being reported. Primaganda High School, Jombang is one of the high schools in Jombang within the Pondok Pesantren environment with moderate exposure to Covid-19 transmission. The risk of transmission during face-to-face learning will be quite high, so there is a need for an integrated management of COVID-19 handling based on proper human resource empowerment. The purpose of community service is to increase empowerment through training. The integrated training was provided for 2 months involving 46 students (referred to as “Genera-Z Tangguh”) as initial movers. Empowerment focuses on preventing the transmission of Covid-19 (education and application of health protocols), and 4T (tracing, texting, testing, treatment) by utilizing digital applications. Activity results include, 1) An increase in the knowledge of Tangguh Genera-Z members about the application of health protocols in schools with an average score of 90 (pre-test mean 30), 2) An increase in knowledge of Tangguh Genera-Z members about 4T cases of Covid-19 with an average post-test score of 70 (pre-test mean 30), 3) The establishment of an integrated Covid-19 handling system related to reporting management and handling of related parties at Primaganda High School Jombang. It can be concluded that this activity is one of the important student social activities and needs to be an example for its application in other schools, to prevent the spread of Covid-19 in the school environment.